Effective harvesting of microalgae by coagulation–flotation - Ling Xia; Yinta Li; Rong Huang; Shaoxian Song (Royal Society Open Science, 2017)
This study developed a coagulation–flotation process for microalgae Chlorella sp. XJ-445 harvesting, which was composed of algal surface modification by combined use of Al3+ and cetyltrimethylammonium bromide (CTAB) and followed dispersed bubble flotation. Dissolved organic matter (DOM) in the medium was firstly characterized and mainly consisted of hydrophilic low molecular weight molecules. The dosage of collector (CTAB) and coagulant (Al3+) were optimized, and with the pretreatment of 40 mg Al3+ and 60 mg CTAB per 1 g dry biomass without pH adjustment, a maximum flotation recovery efficiency of 98.73% can be achieved with the presence of DOM. Algal cells characterization results showed that the combined use of CTAB and Al3+ largely enhanced the algal floc size, and exhibited higher degree of hydrophobicity, which favoured the flotation, and can be interpreted by DLVO (Derjaguin, Landau, Verwey and Overbeek) modelling. A benefit in fatty acid conversion was further found with the optimized coagulation–flotation process. It was suggested that this coagulation based flotation is a promising strategy for high-efficiency harvesting of microalgae.